Theoretical evolution of thesauri: a diachronic study of Dagobert Soergel publications (1972-2017) - Lopes Fujita, Mariangela Spotti [UNESP]; Piovezan Rio Branco, Luciana Beatriz [UNESP]; Vesu Alves, Roberta Caroline [UNESP] (Univ Zaragoza, 2020)
Study on the evolution of thesaurus theory in Dagobert Soergel's discourse. The articles he published on the subject were analyzed using Bardin's content analysis with a diachronic sample. The following categories were considered: construction, functions, maintenance, technologies and uses of thesaurus in the researcher's discourse. The articles showed that Soergel is concerned with scientific and methodological improvement of thesauri in different technological environments. The researcher is innovative and follows the more innovative trends on the construction, functions, maintenance, technologies and uses of thesauri, which and points to their structured development and use in new interoperable technological environments.
Keywords: Soergel; Dagobert; Thesauri; Evolution; Theory